PENGARUH LATIHAN PUSH UP DAN PULL UP TERHADAP PASSING ATAS BOLA VOLI PADA SISWA SMP NU AROSBAYA BANGKALAN - Februandika, Miftakul Kevin; Purwoto, Septyaningrum Putri; Widodo, Haryo Mukti; Handayani, Heni Yuli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Overhead passing is a fundamental skill that is highly important in this game. Overhead passing skill requires strength and endurance of the upper body muscles, which can be improved through physical exercises such as push-ups and pull-ups. This study aims to evaluate the influence of push-up and pull-up exercises on the overhead passing ability in volleyball among students at SMP NU Arosbaya Bangkalan. The research method used was an experiment with a pretest-posttest control group design. Thirty students were randomly selected and divided into two groups: the experimental group and the control group, and the duration of this study was 8 weeks. The results showed a significant improvement in overhead passing ability in the experimental group compared to the control group. The average overhead passing score in the experimental group increased from 18.4 at the pretest to 20.6 at the posttest, while in the control group, it only increased from 17.2 to 17.4. In conclusion, push-up and pull-up exercises are effective in improving overhead passing ability in volleyball, thus, it is recommended to be implemented in volleyball training programs at schools.Top of FormBottom of Form